Physical and chemical characterization of sweet passion fruits genotypes in Sao Mateus, Espírito Santo State, Brazil - Alexandre, Rodrigo Sobreira; Monteiro Junior, Kleber Rogeres; Chagas, Kristhiano; Siqueira, André Lucas; Schmildt, Edilson Romais; Lopes, José Carlos (Comunicata Scientiae, 2018)
In Brazil 95% of the passion fruit marketed comes from the species Passiflora edulis f. flavicarpa (yellow passion fruit), the remainder are Passiflora edulis f. edulis (purple passion fruit) and Passiflora alata (sweet passion fruit), considered market niches. Because of the wide genetic variability the genus Passiflora, it is of fundamental importance to identify superior genotypes to improve the quality of fruit for the fresh market. The objective is to analyze the physical and chemical characteristics of the fruits of 33 genotypes P. alata Curtis, evaluated in a randomized complete block design with two replicates of four plants, from native matrices, located at the experimental farm of the University Center of the North of Espírito Santo, Federal University of Espírito Santo, in the Northern Region of the state of Espírito Santo, São Mateus -ES. Thirty-two mature fruits were collected in each replicate, eight per plant and the following characteristics were analyzed: fruit weight (g); equatorial and polar diameter of fruit (cm); peel thickness (mm); mass of the pulp (g); pulp volume (mL); pulp yield (%); number of seeds per fruit, pH; soluble solids (SS); titratable acidity (TA) and ratio (SS/TA). There is a wide genetic variability among P. alata genotypes as to the traits assessed. Genotypes 4, 6, 8, 11, 15, 18, 21, 25 and 26 stood out among the rest, and is therefore recommended for new plantings and future breeding programs.